2009
DOI: 10.3354/meps08211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flood frequency, temperature and population density on migration of Fundulus heteroclitus in semi-isolated marsh pond habitats

Abstract: Fish respond to habitat and demographic factors that affect growth and survival through migration, reproduction and mortality. However, the importance of migration rates on fish population dynamics and the effects of habitat and demographic factors on movement are not well understood. We used mark-recapture to determine population dynamics (recruitment, mortality, immigration and emigration) of the mummichog Fundulus heteroclitus inhabiting semi-isolated ponds in a New Jersey salt marsh over the spring and sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…This is the first study to characterize continuous changes in pond temperatures and salinities across tide stages and seasons. Water temperatures averaged across tide stages in the PIE‐LTER ponds (Table ) were similar to summertime values in New Jersey marsh ponds [ Hunter et al , ] but slightly cooler than in Virginia ponds during summer and fall [ Layman et al , ]. Salinities were similar across tide stages in the PIE‐LTER ponds (Table ) but increased during tidally isolated periods in several Texas marsh ponds [ Miller et al , ].…”
Section: Discussionmentioning
confidence: 62%
“…This is the first study to characterize continuous changes in pond temperatures and salinities across tide stages and seasons. Water temperatures averaged across tide stages in the PIE‐LTER ponds (Table ) were similar to summertime values in New Jersey marsh ponds [ Hunter et al , ] but slightly cooler than in Virginia ponds during summer and fall [ Layman et al , ]. Salinities were similar across tide stages in the PIE‐LTER ponds (Table ) but increased during tidally isolated periods in several Texas marsh ponds [ Miller et al , ].…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, potential cryptic environmental variables among ponds may be of similar, or higher, importance as the documented temperature and dissolved oxygen differences. For example, Hunter et al [50, 51] demonstrated that tidal pond flooding frequency is significantly, positively correlated with female F. heteroclitus gonadosomatic index. The authors suggest that increased nutrient availability, introduced by frequent tidal flooding, may allow for higher reproductive allocation, a key life-history and fitness related trait.…”
Section: Discussionmentioning
confidence: 99%
“…Estuaries inhabited by F. heteroclitus consist of multiple niches with contrasting environmental parameters. In addition, cryptic differences among seemingly similar niches further exacerbate environmental heterogeneity [4951,64]. Given this patchy landscape and annual panmictic breeding, it is possible that both the significant temporal allele frequency changes as well as spatial divergence observed in the F. heteroclitus system could be explained by Levene’s model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations